Clinical phenotype and genotype analysis of progressive familial intrahepatic cholestasis type 3 caused by novel ABCB4 gene mutation - Ye, X L (Zhonghua er ke za zhi = Chinese journal of pediatrics, 2024)
Objective: To investigate the pathogenic mechanism and clinical characteristics of the novel splicing variant of ATP-binding cassette subfamily B member 4 (ABCB4) and provide a basis for subsequent genetic diagnosis. Methods: The clinical data of a 5-year-old child with cholestatic liver disease admitted to the Beijing Children's Hospital of Capital Medical University was retrospectively analyzed. The pathogenic variations were detected by whole exome sequencing and verified by Sanger sequencing, and bioinformatics was used to predict the pathogenicity of the mutation sites. Possible pathogenic variations were verified in vitro by Minigene assay. The clinical outcome was followed after discharge from hospital. Results: The 5-year-old boy had developed cholestasis at the age of 11 months. His physical examination showed obvious enlargement of the liver and spleen. Cholestatic cirrhosis was diagnosed by liver function tests, abdominal ultrasonography, liver biopsy and pathology. The results of genetic analysis showed that the patient was a complex heterozygote of the ABCB4 gene, with a pathogenic mutation c.2860G>A and a novel mutation c.2065-8T>G, derived from the mother and father respectively. The conservative prediction of the c.2065-8T>G site showed that this region was highly conserved and may affect splicing. Minigene assay results confirmed that the c.2065-8T>G mutation resulted in a 7 bp retention of intron 16 in the mature mRNA. In the absence of nonsense-mediated mRNA decay, the amino acid frameshift forms a truncated protein, which is represented by p.Glu689ValfsTer19. The patient was diagnosed as progressive familial intrahepatic cholestasis type 3 (PFIC3) and treated with ursodeoxycholic acid (UDCA). His clinical symptoms improved during 18 months of follow-up. Conclusions: The c.2065-8T>G variant is confirmed to affect the splicing process and exhibits complex heterozygosity with c.2860G>A, which is identified as the cause of the disease. PFIC3 children with this variant showed cholestatic liver disease as the main manifestation with a slow progression and was sensitive to treatment with UDCA